La malattia perinatale e il contesto familiare: prospettive diagnostiche e terapeutiche - Lucarini, Emanuela; Sassi, Emanuele (Il sogno della farfalla, 2019)
Peripartum psychiatric pathologies (during pregnancy and the first year of life) encompass a wide array of psychopathological manifestations which differentiate depending on different factors such as time of onset (before or after labor), severity and type of clinical picture. In particular, perinatal depression is considered a public health issue. This is due to its high incidence and to the consequences on women’s health and wellbeing, considering both the quality of mother-newborn and couple’s relationship. The most recent epidemiological data show that between 10% and 20% of new mothers develop depressive symptoms during pregnancy and in the post-partum. This represents one of the most common medical complications during pregnancy and puerperium. The aim of this article is to examine the main peripartum pathologies in order to provide clear and useful notions through a diagnostic and preventive perspective.